Kuliner Nusantara dalam Media Sosial: Strategi Pengemasan Pesan Akun Tiktok @adhityaputratama tentang Makanan Tradisional Indonesia - Fany Apbariantika; Andre Noevi Rahmanto (Jurnal Komunikasi Massa, 2025)
This study aims to reveal the message design strategy uploaded by food influencers through the Tiktok platform. Meanwhile, there is a content creator who has succeeded in seizing the public's attention with uploaded culinary content of Indonesian cuisine, namely Yusuf Adhitya Putratama with Tiktok username @adhityaputratama. Adhitya is a pioneer of content creators who focus on uploading legendary Indonesian cuisine. The message design strategy in this study is divided into two parts; the content creation process and the message and creative strategy. This research uses a qualitative method with a descriptive approach and content analysis with observation, interview, and documentation techniques to support the objectives of this research. The results show that the content formation process is well planned. The plan is divided into five stages; research and observation, determining the structure and flow of content, determining information points, video shooting, editing, and review. Meanwhile, the message strategy in this study found that inference in the content is carried out in two sided argument, indirectly Tiktok users will draw their own conclusions regarding the Indonesian culinary content uploaded by Yusuf Adhitya Putratama. In addition, the creative strategy found that the message conveyed could increase purchasing motivation.